Comparison Study on Antioxidant Capacity of Chromolaena Odorata Leaves Extract Obtained from Maceration and Ultrasound-assisted Maceration - Mohammad, Ibrahim Khalil; Mansur, Sity Aishah; A Razak, Aliff Hisyam; Mohd Fauzi , Noor Akhmazillah; Mohd Kassim, Angzzas Sari (Progress in Engineering Application and Technology, 2022)
Chromolaena odorata L. have been categorised as one of the highly serviceable plants in the medicinal field because of its significant antioxidant properties that can greatly enhance the wound healing process. The excellent antioxidant capacity of C. odorata is mainly contributed by its high content of bioactive compound called antioxidants. Antioxidants can be obtained from plant through various extraction process, however the study to determine the optimum method for highest antioxidant activity per extract yield have not much been pursued in the research scene especially extraction method that make use of two different extraction techniques. Therefore, this study aims to explore the effectiveness of applying two different extraction technique (ultrasound-assisted extraction and maceration extraction) on the extract yield and antioxidant capacity. In this study, the content of C. odorata was extracted by maceration and ultrasound-assisted maceration at two different extraction time, 48 hours and 120 hours. The extraction process was conducted using distilled water as solvent and is maintained at 34℃. The extracts were then dry weight for yield assessment. For this study, the extracts were qualitatively assessed for their antioxidant capacity by DPPH and FRAP assay. Based on gallic acid and ascorbic acid standard curve, the antioxidant capacity of every extract was visually graphed for comparison. In this study, ultrasonic-assisted maceration has been shown to be more efficient in extracting process compared to maceration as the yields are higher for both extraction time. When comparison between the extraction time applied, the 120 hours extraction time successfully extracted more compounds from the C. odorata at 87.36% and 27.70% for the ultrasound-assisted maceration and maceration respectively, when compare to the 48 hours extraction time with 65.94 % for ultrasound-assisted maceration and 13.26 % for maceration. In antioxidant assay, all four extracts were observed to exhibit antioxidant capacity with the order antioxidant capacity of both assays are the same at maceration (48 hours) > maceration (120 hours) > ultrasound assisted maceration (48 hours) > ultrasound assisted maceration (120 hours). Quantification of gallic acid and ascorbic acid by using spectrometry as to determine the antioxidant content in the extracts. It established that gallic acid and ascorbic acid made up of about approximately one-fifth of C. odorata.  This study shows that C. odorata has the potential as antioxidant source and the findings may be used for the development of medicinal products from this useful weed.